Electroanatomic mapping‐guided localization of alternative right ventricular septal pacing sites in children. Issue 9 (9th August 2018) - Silvetti, Massimo Stefano; Battipaglia, Irma; Pazzano, Vincenzo; Saputo, Fabio Anselmo; Ravà, Lucilla; Ammirati, Antonio; Calvieri, Camilla; Ciani, Michele; Drago, Fabrizio
Abstract: Background: Alternative right ventricular (RV) sites (RVAPS) have been proposed to prevent or reduce RV pacing‐induced left‐ventricular (LV) dysfunction. Nonfluoroscopic 3D electroanatomic mapping systems (EAM) have been developed to guide cardiac catheter navigation and reduce fluoroscopy during electrophysiological procedures or pacemaker implantations. Aim: The aim of the study was to compare the results of EAM‐guided permanent pacemaker implantation aiming at RVAPS with conventional fluoroscopic‐guided implantation in RV apex (RVA) in children and adolescents. Methods: A prospective, randomized analysis was performed on children/adolescents with complete atrioventricular block (CAVB) who underwent EAM‐guided pacemaker and transvenous leads implantation into RVAPS (EAM‐RVAPS) or conventional, fluoroscopic‐guided implantation into RV apex (RVA). In EAM‐RVAPS, a pacing map guided the implantation of ventricular leads in septal sites with narrower QRS. After implantation, LV contractility (ejection fraction [EF], Global Longitudinal Strain [GLS]) and synchrony were evaluated at 1–12 months. Results: Twenty‐one pediatric patients with CAVB, with (six patients) or without structural heart diseases, aged 4–16 (median 10.5) years, were divided in two groups: EAM‐RVAPS (11 patients, four dual‐chamber/DDD, seven single‐chamber/VVIR pacemakers) and RVA (10 patients, one DDD/nine VVIR). The two groups did not show significant differences for preoperative parameters. EAM‐RVAPS showed: preserved LVEF and synchrony (not significantly different than RVA), significantly lower GLS and radiation doses/exposures, in spite more complex procedures, significantly longer procedure times and narrower paced QRS than RVA. Conclusions: EAM‐guided procedures have been useful to reduce radiation exposure and to localize RVAPS with narrower paced QRS and lower GLS than RVA.